Sifat Fisika Mekanika Briket Arang dengan Komposisi Jenis Kayu Gerunggang (Cratoxylon arborescens) dan Kayu Tumih (Combretocarpus rotundatus) - Alpian Alpian; Raynold Panjaitan; Adi Jaya; Yanciluk Yanciluk; Wahyu Supriyati Supriyati; Emmy U. Antang (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
Energy is a major component in human daily life so it is needed in daily activities and production. The main source of energy used today comes from fossils such as petroleum, natural gas and coal which are non-renewable, unsustainable, limited in existence and can damage the environment. One of the more environmentally friendly and renewable energy substitutes is charcoal briquettes. The raw material used for the manufacture of charcoal briquettes is charcoal powder from biomass waste in land clearing in the Village of Kalampangan, Palangka Raya City. The fire burn the Kalampangan urban area in 2015. The burning area makes succession and overgrown of pioneer plants such as Gerunggang and Tumih that cannot use maximum. Both types of wood can be used as material for making charcoal briquettes. The purpose of this study is to determine the physical and mechanical properties of charcoal briquettes produced from biomass waste without burning fuel with several raw material compositions from Gerunggang and Tumih charcoal powders. The charcoal briquettes refer to the Indonesian National Standard (SNI 01-6235-2000) and ESDM Permen No. No. 047 of 2006. The number of treatments was 5 (T100: G0; T25: G75; T50: G50; T75: G25 and T0: G100) of 3 replications. The composition with the most potential test results in accordance with the both of standards that used is the composition of T100: G0 with a lower moisture content of 10.10%, density 0.98 g/cm3, and compressive strength 25.68 kg/cm2.